Potential of Combined Power Flow Generation on Basis of Belarusian Heat Technologies - V. N. Romaniuk; D. B. Muslina; A. A. Bobich; N. A. Kolomytskaya; A. V. Romaniuk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers potential of power saving by the Belarusian industrial enterprises at transition to cogeneration power supply of heat technological processes.